THE INFLUENCE OF MIXTURES OF GROWTH REGULATORS AND FUNGICIDES ON THE SPRING RAPE SEEDS YIELDS AND QUALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Our trial aims at investigating the impact performed by the mixture of a growing-regulator and fungicides upon summer rape productivity, the crop structure, and quality, to justify applying of agrochemicals in smaller doses thus eliminating environment pollution and winning labour-saving resource and financial applying per unit of sowing- fields, and per unit of the gained production. In 2001 – 2003, Research institute of Agriculture preparations during the trial were tested applying half doses (0,5 1 ha–1), creating the preparation mixtures: Moddus+ Folicur, Modus + Juventus; Cycocel + Folicur Cycocel + Juventus, through spraying them throughout plant florescence-bud formation (GS 50). Owing to the mixtures of preparations, the number of side branches increased, on average, for 1-2, the number of legumes on a plant – for 22-25, the number of seeds per legume for 2- 4, the mass o f 1000 seeds: from 3,7 to 4,2 g, at the same time the length of rape”s stem”s shorted down to 10-20 cm, and the branching height to 5-14 cm. The highest efficiency, however, was reached when applying the mixture of Cycocel and Juventus.On average, throughout all the three years, thanks to applying of growing-regulators and fungicides the summer oilseed rape harvesting essentially increased, if compared to the Control. The increase of harvest was 0,53-0,81 t ha –1 (γ0,05 0,24 t ha-1). During the trial-years the very best preparation mixture was nominated, and it was the Cycocel + Juventus, which, on average, provided the seed harvest 3,31 t ha –1, and the oil output 1409 kg ha –1. Other mixtures ensured a related seed output – 3,03-3,15 t ha –1, and the oil output 1270-1302 kg ha–1.